Magnetowetting and sliding motion of a sessile ferrofluid droplet in the presence of a permanent magnet - Nguyen, Nam-Trung (2012)
Motion of a droplet on a planar surface has applications in droplet-based lab on a chip technology. This paper reports the experimental results of the shape, contact angles, and motion of ferrofluid droplets driven by a permanent magnet on a planar homogeneous surface. The water-based ferrofluid in use is a colloidal suspension of single-domain magnetic nanoparticles. The effect of the magnetic field on the apparent contact angle of the ferrofluid droplet was first investigated. The results show that an increasing magnetic flux decreases the apparent contact angle of a sessile ferrofluid droplet. Next, the dynamic contact angle was investigated by observing the shape and the motion of a sessile ferrofluid droplet. The advancing and receding contact angles of the moving ferrofluid were measured at different moving speeds and magnetic field strengths. The measured contact angles were used to estimate the magnitude of the forces involved in the sliding motion. Scaling analysis was carried out to derive the critical velocity, beyond which the droplet is not able to catch up with the moving magnet.